PERAN SALURAN DISTRIBUSI DAN AKTIVITAS PEMASARAN SOSIAL MEDIA DALAM MENINGKATKAN KINERJA PEMASARAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Suriyanti; Rahmad Solling Hamid; Riska Eka Putri Bachtiar; Riefky Dj Al Idrus (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2024)
The role of distribution channels and social media marketing activities is crucial in boosting the marketing performance of SMEs (small and medium enterprises). By integrating efficient distribution channels and robust social media marketing strategies, SMEs can expand their market reach, strengthen their brand image, and increase marketing effectiveness and sales volume. Through the proper use of distribution channels and effective utilization of social media, SMEs can foster closer relationships with their consumers, enhance customer loyalty, and sustainably expand their market share. Thus, a balanced combination of distribution channels and social media marketing is key to the success of SMEs in enhancing competitiveness and growth in this digital era. This study aims to examine the role of distribution channels and social media marketing activities in improving the marketing performance of small and medium enterprises (SMEs). The sample used in this study consisted of 100 SMEs. The method of analysis used to test the hypotheses in this study was multiple linear regression. This research yields important information that, partially, distribution channels and social media marketing activities have proven to play a significant role in enhancing the marketing performance of SMEs.